Strategie marketingowe na rynkach zagranicznych - Skulski, Przemysław (Marketing Strategies on Foreign Markets, 2008)
The distinguishing feature of the literature devoted to marketing strategies - including international ones - is a variety of approaches to this issue. As a result, there are plenty of different views pertaining to both the essence of marketing strategies and their classifications. The role of the procedure of international marketing strategy formation is underlined in many papers. Such a procedure ought to be designed to make companies more creative in terms of problem solving. It should be also borne in mind that lots of authors emphasise the individual character of marketing strategies which is associated - among others - with the volatility of the international environment, specific character of firms, sectors as well as local markets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 185-194